Relationship between sustainable buying intention and marketing strategies - Lizbeth Salgado-Beltrán; María E. Subira-Lobera; Luis F. Beltrán-Morales (The International Journal of Management Science and Information Technology (IJMSIT), 2014)
In this paper, we analysed the relationship between sustainable buying intention (SBI) and marketing strategies (price, product, communication and placement) and We use a theoretical model to test hypothesis via structural equation model by maximum likelihood in AMOS version 19.0 software. Sampling (N=524) was performed at sale points of the business premises where volunteer participants answered a structured questionnaire in the five-point Likert scale. The results show a strong association with marketing strategies and sustainable buying intention, so the price is still a very important factor when purchasing. The managerial implication of this study more relevant would focus on the importance for companies to recognize that marketing strategies are assets which have to invest more effort.
Keywords: 650; marketing strategies; sustainable buying intention; Structural equation model; green marketing; corporate social responsibility